T regulatory cells and their counterparts: masters of immune regulation - (:unkn) unknown (WILEY, 2009)
The interaction of environmental and genetic factors with the immune system can lead to the development of allergic diseases. The essential step in this progress is the generation of allergen-specific CD4(+) T-helper (Th) type 2 cells that mediate several effector functions. The influence of Th2 cytokines leads to the production of allergen-specific IgE antibodies by B cells, development and recruitment of eosinophils, mucus production and bronchial hyperreactivity, as well as tissue homing of other Th2 cells and eosinophils. Meanwhile, Th1 cells may contribute to chronicity and the effector phases. T cells termed T regulatory (Treg) cells, which have immunosuppressive functions and cytokine profiles distinct from that of either Th1 or Th2 cells, have been intensely investigated during the last 13 years. Treg cell response is characterized by an abolished allergen-specific T cell proliferation and the suppressed secretion of Th1 and Th2-type cytokines. Treg cells are able to inhibit the development of allergen-specific Th2 and Th1 cell responses and therefore play an important role in a healthy immune response to allergens. In addition, Treg cells potently suppress IgE production and directly or indirectly suppress the activity of effector cells of allergic inflammation, such as eosinophils, basophils and mast cells. Currently, Treg cells represent an exciting area of research, where understanding the mechanisms of peripheral tolerance to allergens may soon lead to more rational and safer approaches for the prevention and cure of allergic diseases.
Keywords: GROWTH-FACTOR-BETA; BEE VENOM IMMUNOTHERAPY; DENDRITIC CELLS; CUTTING EDGE; B-CELLS; TYROSINE PHOSPHORYLATION; SPONTANEOUS-ABORTION; TOLERANCE INDUCTION; SUPPRESSOR FUNCTION; ASTHMATIC REACTIONS